Modelo para o Projeto de Planos de Ensino em Plataformas Computacionais Móveis - Santos, Mateus dos (2018)
Mobile platforms can provide teaching programs that favor student learning. The characteristics of autonomy and personalization of mobile devices are factors that reinforce this. However, designing a teaching program requires an increased attention from the educator due to the particularities of the mobile platforms. This proposal presents a model for projects of mobile teaching studies. This model presents six steps for the elaboration of study plans considering as characteristics of autonomy of the student. This model was tested through an application for data storage machines and the application of tools for the use of a search engine tool. The application was designed according to the steps determined by the model and tested with the group of people. The results of the tests were satisfactory, thus concluding a viability of the proposed model. These charges refer to the use of the model for other systems that use mobile platforms.